Kajian Awal Proses Konversi Limbah Plastik Menjadi Bahan Bakar Alternatif Menggunakan Alat Sederhana pada Skala Praktikum - Tarigan, Junita; Raju, Raju (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2026)
Plastic waste has become an increasingly serious environmental problem due to the high consumption of plastic materials and their resistance to natural degradation. On the other hand, plastics contain a high proportion of hydrocarbons, making them potentially suitable as alternative energy sources through thermal conversion processes. This study aims to explore the conversion of plastic bottle waste into liquid fuel using a simple apparatus at a practicum scale. An experimental approach was employed with descriptive observations focusing on process duration and heating temperature characteristics. The conversion system was designed using simple components, consisting of a metal can reactor, a plastic hose as a gas outlet, a cooling system utilizing ice as the cooling medium, and a container for collecting condensed products. Plastic waste was heated using a stove as the heat source, and reactor temperatures were recorded at 10-minute intervals until the conversion process ended. The results showed that the reactor temperature increased gradually and reached a maximum of 360.1 °C, which falls within the active pyrolysis temperature range. From an initial plastic mass of 300 g, 6 g of liquid fuel was produced with a yield of 2%, along with 82 g of solid residue. The relatively low liquid yield indicates limitations in heat distribution and condensation efficiency within the simple system. Combustion tests demonstrated that the produced liquid fuel was able to burn stably for 3 minutes and 17 seconds with an orange-reddish flame, indicating the presence of combustible hydrocarbon fractions. This study demonstrates that plastic waste conversion into liquid fuel can be directly observed using simple equipment at a practicum scale, supporting energy conversion learning and providing a basis for further research with improved system design.